DEVELOPMENT OF THE WESTERN CASPIAN MARITIME TRADE IN THE FIRST HALF OF THE 18th CENTURY - Abdusalamov, M-P B; Magaramov, S A; Halaev, Z A (History, Archeology and Ethnography of the Caucasus, 2017)
The article deals with the development of trade contacts between Russia and Oriental countries that were carried out through the western and southern coasts of the Caspian Sea in the first half of the 18th century. Since the early Middle Ages, the Russians had been contacting with the population of the Caspian Sea regions and Oriental countries via the Volga-Caspian Route. The western coast of the Caspian Sea, in contrast to the eastern one, had significant merchant harbors (Derbent, Nizabad, Baku), which accounted for a great part of international trade turnover. Since the beginning of the 18th century, the transit role of the Caucasian coast of the Caspian Sea had been increasing, Russia was interested in establishing trade and economic contacts with the East, as the main commodity of the Eastern trade - silk - was to be exported to European countries via the Caspian-Volga Route. Therefore, measures were taken to reconstruct the merchant harbors, particularly in Derbent and Baku, the required infrastructure along the western and southern coasts of the Caspian Sea was created, the Caspian flotilla was modernized, and more weight-lifting vessels were built and replaced the busses of the previous century. Transportation of cargo across the Caspian Sea was quite a profitable business, and it was carried out only by Russian sea-going vessels that had been built in the Astrakhan Admiralty established on the order of Peter I. The Caspian trade with the countries of the Caucasus and the Western Caspian Sea regions continued developing in the post-Petrine period. During the period of the Caucasian conquests, Nadir Shah planned to create a strong fleet in the Caspian Sea like that of Russia. For this purpose, the representatives of the English company, Hanway and Elton, were employed by Nadir Shah and were allowed to build ships and sail on merchant ships over the Caspian Sea. However, the Iranian Shah’s plans to create his own fleet in the Caspian Sea, as well as his Dagestan campaign failed.